Criminal Law Enforcement on Illegal Access to Bank Customer Data: A Study at the South Sulawesi Regional Police - Dodik Susianto; La Ode Husen; Zainuddin Zainuddin; Muh. Zulkifli Muhdar (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study aims to analyze criminal law enforcement against perpetrators of illegal access to bank customer data at the South Sulawesi Regional Police and to identify the factors influencing its effectiveness. The research employs an empirical legal method with a normative-empirical approach, examining the relationship between legal norms and their implementation in practice. Data were collected through library research, interviews, and document studies, using both primary and secondary legal materials. The findings reveal that criminal law enforcement has been implemented through investigation and inquiry processes based on the Law on Information and Electronic Transactions, the Banking Law, and the Personal Data Protection Law. However, its effectiveness has not yet been fully optimal due to several obstacles, including limited human resource capacity, inadequate digital forensic facilities, the complexity of electronic evidence, weak inter-agency coordination, rapid technological developments, and low public awareness of digital security. The study concludes that strengthening adaptive regulations, improving investigator competence, enhancing digital forensic infrastructure, and intensifying coordination among law enforcement agencies, banking institutions, and regulatory bodies are essential to achieving more effective and professional law enforcement. Public education on personal data protection is also necessary to support preventive efforts against cybercrime in the banking sector